To add the two expressions, we simply combine like terms.
The first expression is 4d - 3, and the second expression is 12d + 4.
We can then add the like terms:
(4d - 3) + (12d + 4) = 4d + 12d - 3 + 4 = 16d + 1
So the sum is 16d + 1.
Add: (4d−3)+(12d+4) . (1 point)
3 answers
Add: (2m−3)+(3n−1)+(3m+1) .(1 point)
To add the three expressions, we will perform the addition operation on each term.
The first expression is 2m - 3, the second expression is 3n - 1, and the third expression is 3m + 1.
Let's add the three expressions:
(2m - 3) + (3n - 1) + (3m + 1)
= 2m + 3n - 1 + 3m + 1
= (2m + 3m) + 3n + (-1 + 1)
= 5m + 3n
So, the sum of the three expressions is 5m + 3n.
The first expression is 2m - 3, the second expression is 3n - 1, and the third expression is 3m + 1.
Let's add the three expressions:
(2m - 3) + (3n - 1) + (3m + 1)
= 2m + 3n - 1 + 3m + 1
= (2m + 3m) + 3n + (-1 + 1)
= 5m + 3n
So, the sum of the three expressions is 5m + 3n.